ANALISIS PENGARUH CAMPURAN BIOETANOL LIMBAH KEDELAI DENGAN PERTALITE TERHADAP DAYA DAN EMISI MOTOR 155 CC: ANALYSIS OF THE EFFECT SOYBEAN WASTE BIOETHANOL ANDPERTALITE ON POWER AND MOTOR EMISSION OF 155 CC - Dimas Yuwafi Ardiansyah (Jurnal Teknik Mesin, 2022)
The increase in vehiclesis directly proportional to the increase in fuel oil as a source of vehicle propulsion.The government's efforts are to support new and renewable energy fuels, one of which is bioethanolThe purpose of the study was to determine the effect of adding a mixture of soybean waste bioethanol and pertalite on emission tests and vehicle powertests.By mixing soybean waste bioethanol and pertalite. The ethanol is 92%. The percentage of bioethanol waste bioethanol (0,10,20,30%) and in vehicle engine rotation (3000-6000 rpm). This study concludes that the addition of bioethanol with RON 92 fuelaffects increasing power and decreasing levels of hydrocarbon and carbon monoxide emission gases. obtained power of 4.09 Hp at 6000 rpm engine speed with a 10% bioethanol mixture. Obtained a decrease in Hydrocarbon content of 89 ppm at 5000 engine speedwith a 30% bioethanol mixture, and a decrease in carbon monoxide levels of 0.13% at 6000 engine speed with a 30% bioethanol mixture.